Competency of School Administrators According to Thailand 4.0 Policy - Moonmaungsan, Jirapat; Saiyasopon, Sukhumvit (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to study the competency of school administrators in Udon Thani province to Thailand 4.0 policy, 2. to assess the competency level of school administrators in Udon Thani province to Thailand 4.0 policy, 3. To find ways to develop the competency of school administrators in the province. Udon Thani towards Thailand 4.0 policy. The samples group in the research School administrators under the Secondary Educational Service Area Office 20 and the UdonThani Primary Educational Service Area Office 1, tallying 162 respondents. The instrument used for the research was the five-rating questionnaire. Statistics utilized for processing data embraced frequency, percentage, means and standard deviations. The results of the study showed that : 1. The competence of educational institution administrators in Udon Thani province consisted of 13 main components, overall at the highest level. 2. Guidelines for the development of school administrators' competency in accordance with the Thailand 4.0 policy. 1. Knowledge. School administrators should always study for new knowledge. Training should be provided for the use of education laws at least annually. 1-2 times. 2. Skills. School administrators should establish a policy of using English for internal communication at least 1-2 days a week to train the skills for themselves and their personnel. In the school Encourage teachers Students use English for communication. 3. As for the characteristics, school administrators should be good models. Whether it is personality, posing, acting respectfully By diligently training yourself Reduce bad example actions, etc., should arrange training on ethics and morality programs related to school administrators at least 1-2 times a year.